Algorithm for the development of a multicomponent pharmaceutical substance of plant origin with antimicrobial action: from science search to dosage form - V. A. Filatov; O. Yu. Kulyak; E. I. Kalenikova (Разработка и регистрация лекарственных средств, 2024)
Introduction. Despite the proven clinical efficacy of antifungal and anti-inflammatory drugs for the prevention and treatment of seborrheic dermatitis, the search for new targets and the development of new substances with a beneficial effect on the scalp microflora, with a low risk of antimicrobial resistance and adverse effects, are relevant.Aim. Development of the antimicrobial multicomponent pharmaceutical substance of plant origin in stages: from a literature search for promising substances, analysis of their composition by GC-MS, in silico evaluation of the affinity of individual components to pathogenetic targets, selection of the optimal composition of a multicomponent substance based on the results of in vitro research of antimicrobial action and the making of a medical dosage form based on it – a medicinal shampoo for the treatment of seborrheic dermatitis.Materials and methods. Objects of research: tea tree essential oil, 1,8-cineole, α-(-)-bisabolol and the multicomponent substance based on them. Methods: molecular docking (AutoDock version 4.2), prediction of pharmacological activity (Phyto4Health), TLC, GC-MS, study of antimicrobial activity in vitro.Results and discussion. Based on the results of a literature search, 3 promising substances were selected for the development of a multicomponent plant-based substance: tea tree essential oil, 1,8-cineole and α-(-)-bisabolol. Molecular docking predicted the targeted activity of the phytochemicals of tea tree essential oil, 1,8-cineole and α-(-)-bisabolol on the domains of ABC-transporters of microorganisms involved in the pathogenesis of seborrheic dermatitis and justified the possibility of use for therapy. The multicomponent substance has been developed based on tea tree essential oil, 1,8-cineole and α-(-)-bisabolol in a mass ratio of 1 : 1 : 1. The qualitative composition of the substance was assessed by TLC and GC-MS methods, and 15 terpenes were quantitatively identified in its composition with a predominance of terpinen-4-ol (16.98 %), 1,8-cineole (25.63 %) and α-(-)-bisabolol (27.67 %). The synergistic antimicrobial activity of the substance has been established against S. epidermidis, S. aureus, C. albicans and M. furfur in comparison with benzalkonium chloride, ketoconazole and climbazole. The composition of a new medical shampoo based on the investigated substance has been developed, which has a pronounced antifungal effect (more than 99.0 %) against M. furfur without visible suppression of normal microflora. For the novel substance of plant origin and medical shampoo, quality parameters were assessed in accordance with the Russian Pharmacopoeia of XIV edition.Conclusion. A substance of plant origin with synergistic and targeted antimicrobial activity has been developed. It has an interest for further study as a drug and API for new products for the treatment of seborrheic dermatitis.